Traditional use of plants by the Magar community in Arghakhanchi District, Nepal (Botanica Orientalis: Journal of Plant Science, 2025)
The ethnobotanical reservoir of local people, which has survived and adapted over the centuries, is usually very rich with precise knowledge about various plants and their use for different purposes. This study aims to document the traditional knowledge related to plant use among the Magar ethnic group of Arghakhanchi District, central Nepal. Fieldwork was carried out to document the plants used by the Magar people of Chhapdanda and Dharapani villages through key informant interviews. The results revealed that the Magar people were using 137 plant species for different purposes, with 102 species identified in Chhapdanda and 100 in Dharapani. A total of 131 species were identified as medicinal. Gastrointestinal disorder was the most common ailment treated by plants. Among other ethnobotanical uses, the Magar people, combining both villages, identified 35 species of plants used as food, 20 as material sources, 15 for religious and spiritual purposes, 7 for alcoholic beverages preparation, 7 as fodder, and 4 as food additives. Sixty-nine plant species were cited for more than one ethnobotanical use category, with Diploknema butyracea having the highest number of ethnobotanical uses. Naturally, the Magar people of Arghakhanchi District are rich in their traditional knowledge, particularly concerning the medicinal applications of plants. Safeguarding this knowledge is vital not only to improve the health of the ethnic communities but the entire society in general.